Adventurous cuisine in Laos: Hebeloma parvisporum, a new species in Hebeloma section Porphyrospora. (2nd January 2020) - Eberhardt, Ursula; Beker, Henry J.; Schütz, Nicole; Pedersen, Ole S.; Sysouphanthong, Phongeun; Læssøe, Thomas
ABSTRACT: Hebeloma parvisporum is described as new and placed within H . sect. Porphyrospora . This mushroom is sold as an edible in markets of Laos under the local name "wai khom." Hebeloma sect. Porphyrospora is discussed and expanded to include the species formerly included in the genus Anamika and recently transferred to Hebeloma. Hebeloma sect. Porphyrospora currently comprises 16 species, 14 of which are known only from the western Pacific and Indian subcontinent. All species in this section share the character of having red-brown spores when fresh, atypical for other sections of Hebeloma, which causes the lamellae to be red-brown. However, this red-brown color fades when the material is dried. The close links, morphologically and molecularly, between H. parvisporum and other members of H . sect. Porphyrospora, particularly H. victoriense, are shown.